LITHUANIAN PRIZES FOR LITERATURE AND THEIR IMPACT ON PUBLISHING - Lebednikaitė, Lina (Knygotyra, 2017)
The article is intended to evaluate the current situation of Lithuanian literary prizes. It provides a thorough analysis of the number and type of the current Lithuanian literary prizes and sheds light on the attitude held by Lithuanian publishers towards these prizes and their impact on the publishing industry. The article does not cover such matters as children‘s literary awards, prizes for literary translation, the awards received by other creative artists, book art awards and various literary contests. The study was conducted on the basis of the material collected during the interview conducted with representatives of Lithuanian publishing houses and its subsequent interpretation, using the Claire Squires‘ proposed theory on the role of literary prizes. It is concluded that Lithuanian publishers are hardly aware of the abundance of Lithuanian literary prizes (36), in particular municipal and district municipal awards. However, publishing houses confirm that such prizes are significant in promoting the cultural life and literary needs on the regional level. With regards to the role of literary prizes, only the first role attributed to them is present in Lithuania: the work of a certain creative artist is noticed and valued, but the other opportunities offered by the said literary prizes are not taken advantage of in publishing business. In the context of world prizes, the absence of a marked culture of book discussions in Lithuania is the biggest gap, accounting for poor awareness and unreadiness to make the most of literary prizes – such culture is non-existent in Lithuania. There is a lack of channels for discussing books, a literary award does not attract media attention or it is extremely low. In addition, there is a lack of cooperation between literary prize organizers and publishing houses. The endeavours taken by the Lithuanian publishing houses to make the most of literary prizes should be regarded as favourable factor. However, their efforts are too insignificant, lacking systematic approach and undertaken only in isolated cases, In addition, they do not dare to experiment and risk. The literary prizes which have the potential to create a mass reading interest in literature, are not yet properly taken advantage of in Lithuania.
Keywords: Lithuanian prizes for literature; the importance of prizes in publishing; publishing marketing